Valores e circunstâncias do pensamento geográfico francês (parte um): a “Nouvelle Géographie” segundo os testemunhos de Henri Chamussy e Roger Brunet - Dante F. C. Reis Junior (Confins)
Motivated by the objective of gathering and comparing versions about the meanings and implications of the methodological turn in Geography, between the 1960s and 1970s, we present here a sample of testimonies collected from three important protagonists of scientific change in France. We understand that the value of these personal representations about the events of that time lies in the fact that, although they result from singular experiences and possible idiosyncrasies, because they derive from an a posteriori reflexive appreciation (already distanced from that period), they are very useful both to demonstrate the general characters of the paradigm shift (by the possible confluence of their impressions), and to attest the inherent ambiguities (by virtual dissent). In this first part, we present the testimonies of Henri Chamussy and Roger Brunet, which make us realize two particular dispositions: one, involving a spirit in relative dilemma; another, seeming to indicate a more decidedly transgressive genius.